Phenylbutyrate—a pan-HDAC inhibitor—suppresses proliferation of glioblastoma LN-229 cell line - Kusaczuk, Magdalena (Tumour Biol, 2015)
Phenylbutyrate (PBA) is a histone deacetylase inhibitor known for inducing differentiation, cell cycle arrest, and apoptosis in various cancer cells. However, the effects of PBA seem to be very cell-type-specific and sometimes limited exclusively to a particular cell line. Here, we provided novel information concerning cellular effects of PBA in LN-229 and LN-18 glioblastoma cell lines which have not been previously evaluated in context of PBA exposure. We found that LN-18 cells were PBA-insensitive even at high concentrations of PBA. In contrary, in LN-229 cells, 5 and 15 mmol/L PBA inhibited cell growth and proliferation mainly by causing prominent changes in cell morphology and promoting S- and G2/M-dependent cell cycle arrest. Moreover, we observed nearly a 3-fold increase in apoptosis of LN-229 cells treated with 15 mmol/L PBA, in comparison to control. Furthermore, PBA was found to up-regulate the expression of p21 whereas p53 expression level remained unchanged. We also showed that PBA down-regulated the expression of the anti-apoptotic genes Bcl-2/Bcl-X (L), however without affecting the expression of pro-apoptotic Bax and Bim. Taken together, our results suggest that PBA might potentially be considered as an agent slowing-down the progress of glioblastoma; however, further analyses are still needed to comprehensively resolve the nature of its activity in this type of cancer.